2020
DOI: 10.3390/microorganisms8081143
|View full text |Cite
|
Sign up to set email alerts
|

Optimized MALDI TOF Mass Spectrometry Identification of Francisella tularensis Subsp. holarctica

Abstract: Francisella tularensis is a tier 1 agent causing the zoonosis tularemia. This highly infectious Gram-negative bacterium is occasionally isolated from human samples (especially blood samples) in routine clinical microbiology laboratories. A rapid and accurate method for identifying this pathogen is needed in order to optimize the infected patient’s healthcare management and prevent contamination of the laboratory personnel. MALDI TOF mass spectrometry has become the gold standard for the rapid identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Multiple Shewanella species are frequently isolated from food products and clinical specimens as opportunistic pathogens ( Pagani et al, 2003 ; Liu et al, 2013 ; Janda and Abbott, 2014 ). Commercial systems, such as Vitek and MALDI-TOF MS (bioMérieux, Bruker), are available for species identification in clinical laboratories ( Regoui et al, 2020 ; Sánchez-Juanes et al, 2020 ). However, only a few species, like S. putrefaciens and S. algae , were recorded in the database ( Liu et al, 2013 ; Janda and Abbott, 2014 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple Shewanella species are frequently isolated from food products and clinical specimens as opportunistic pathogens ( Pagani et al, 2003 ; Liu et al, 2013 ; Janda and Abbott, 2014 ). Commercial systems, such as Vitek and MALDI-TOF MS (bioMérieux, Bruker), are available for species identification in clinical laboratories ( Regoui et al, 2020 ; Sánchez-Juanes et al, 2020 ). However, only a few species, like S. putrefaciens and S. algae , were recorded in the database ( Liu et al, 2013 ; Janda and Abbott, 2014 ; Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regoui et al, on the other hand, developed a database to identify Francisella tularensis and distinguished it from the closely related species F. tularensis subsp. novicida and Francisella philomiragia [ 77 ]. They also found that incubation on chocolate agar plates supplemented with PolyViteX ® at 30 or 37 °C in an aerobic or 5% CO 2 -enriched atmosphere for less than 72 h allows for the accurate identification of F. tularensis subsp.…”
Section: Bacteria Identificationmentioning
confidence: 99%
“…A study suggested that some isolates belonging to various genera such as Bacillus, Stenotrophomonas, Pseudomonas, and Rhodococcus were grouped and were differentiated upto strain level by using MALDI-TOF MS however, rep-PCR failed to produce such results (Ghyselinck et al 2011 ). MALDI-TOF MS can classify serotypes of Listeria monocytogenes in three lineages (Ojima-Kato et al 2016 ), differentiated subspecies of Francisellatularensis (Regoui et al 2020 ) as well as discriminated the strains of Legionella (Blanco et al 2021 ). Tanigawa et al ( 2010 ) used mass spectral analysis of ribosomal proteins to distinguish between different Lactococcus species and subspecies.…”
Section: Dereplicationmentioning
confidence: 99%